2022
DOI: 10.21834/ebpj.v7i20.3477
|View full text |Cite
|
Sign up to set email alerts
|

Managing Family and Work: The Search for the Ideal Work-life Balance

Abstract: Employers in the food and beverage (F&B) industry require many high-skilled and well-trained professionals but workers are often exploited in the industry. Aiming to answer if personal health, personal time management, and family matters affect the work-life balance (WLB) of F&B employees, which family matters played a mediator role. The data of 108 responses was analysed through the PROCESS analysis and Sobel's Test. The regression analysis shows that family matters are a mediator of the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…On the other hand, a study among married Pakistani women professionals revealed that long work hours and rigid schedules increase the likelihood of female employees having work-family conflicts (Jostell & Hemlin, 2018;Khursheed et al, 2019). This finding confirms recent research findings that demonstrate a substantial beneficial relationship between Personal Time Management and work-life balance (Saad et al, 2022), thus, to further investigate the association of time management and work-life balance among nurses in public hospitals, this hypothesis is developed. H2: There is a positive relationship between time management and work-life balance among nurses in public health institutions.…”
Section: Work-life Balancessupporting
confidence: 83%
“…On the other hand, a study among married Pakistani women professionals revealed that long work hours and rigid schedules increase the likelihood of female employees having work-family conflicts (Jostell & Hemlin, 2018;Khursheed et al, 2019). This finding confirms recent research findings that demonstrate a substantial beneficial relationship between Personal Time Management and work-life balance (Saad et al, 2022), thus, to further investigate the association of time management and work-life balance among nurses in public hospitals, this hypothesis is developed. H2: There is a positive relationship between time management and work-life balance among nurses in public health institutions.…”
Section: Work-life Balancessupporting
confidence: 83%